Effects of Using the Bilangual (Thai - Malayu) Cartoon Animation on Knowledge and Attitudes Towards Vaccination among Caregivers of Children’ Delayed Vaccination Schedules in Narathiwas Province - Hayeese, Wanisa; mayae, Hamdee (Princess of Naradhiwas University Journal, 2025)
The quasi-experimental research aimed to investigate the effects of using bilangual (Thai-Malayu) cartoon animation on knowledge and attitudes towards age-appropriate vaccinations as well as cartoon animation satisfaction. Samples were 32 parents of children aged zero to five years old who postponed their children's immunization schedules and resided in the Narathiwas province. The design thinking method of: 1) empathizing; 2) defining the problem; 3) ideating; 4) prototyping; and 5) testing was used to develop the bilingual (Thai-Malayu) cartoon animation that served as the trial's instruments. The instruments used to collect the data included a knowledge measurement, and an attitude questionnaire. Data were analyzed by using average, standard deviation, Pair t-test and satisfaction questionnaire. The results showed that samples' average scores of knowledges and attitude toward vaccination were statistically significantly higher after using the program (t = 1.26, t = 1.87, p<0.05, respectively), and they were highly satisfied with the use of the bilingual (Thai-Malayu) cartoon animation (M = 4.54, SD = 1.02). According to the study's findings, caregivers may find it particularly enjoyable to learn from bilingual (Thai-Malayu) cartoon animation since it tells a true story that they can employ in their everyday lives. Additionally, it uses a language that is acceptable for the people living in the three southern border provinces.